An Empirical Analysis on the Influencing Elements of IPO Underpricing in China: New Evidence from Shanghai and Shenzhen Stock Exchanges 2001-2008 - Tong, Qiqi (2010)
This research provides an empirical analysis of the influencing elements of the IPO underpricing on Shanghai and Shenzhen stock exchanges in China. Applying multiple regression technique through PASW Statistics 18, a database of 491 A-Share IPO firms is randomly selected from 29 November 2001 to 25 September 2008.